2019
DOI: 10.3390/en12050959
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Analysis of the Effect of Vortex Generator Height on Vortex Characteristics and Airfoil Aerodynamic Performance

Abstract: To explore the effect of the height of vortex generators (VGs) on the control effect of boundary-layer flow, the vortex characteristics of a plate and the aerodynamic characteristics of an airfoil for VGs were studied by both wind tunnel experiments and numerical methods. Firstly, the ratio of VG height (H) to boundary layer thickness (δ) was studied on a flat plate boundary layer; the values of H are 0.1δ, 0.2δ, 0.5δ, 1.0δ, 1.5δ, and 2.0δ. Results show that the concentrated vortex intensity and VG height pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…From the beginning of the experiment, it was calculated the change in the thickness of the boundary layer starting from the front edge of the flat plate. A speed of flow in the working part of the installation in this experiment was V  = 33 м/с, which corresponded to a Reynolds number Re = 0.89810 6 . The results of the experiment were compared with the obtained that of analytically for a flat plate, where the following relations were used in calculating the thickness of the boundary layer.…”
Section: The Methodology Of the Experimental Researchmentioning
confidence: 95%
“…From the beginning of the experiment, it was calculated the change in the thickness of the boundary layer starting from the front edge of the flat plate. A speed of flow in the working part of the installation in this experiment was V  = 33 м/с, which corresponded to a Reynolds number Re = 0.89810 6 . The results of the experiment were compared with the obtained that of analytically for a flat plate, where the following relations were used in calculating the thickness of the boundary layer.…”
Section: The Methodology Of the Experimental Researchmentioning
confidence: 95%
“…Iowa State University 3 [19] City University of Hong Kong 3 [20] ABRI, National Cheng Kung University 3 [21] DAA, National Cheng Kung University 3 [22] North China Electric Power University 3 [23] Portland State University 2 [24] Ruhr-Universität Bochum 2 [25] Technion Flow Control Lab 2 [26] TU Delft 2 [27] Beijing University of Aeronautics & Astronautics 1 [28] China Aerodynamic Research and Development Center 1 [29] IET, Chinese Academy of Sciences 1 [30] Inter-University Research Centre on Building Aerodynamics and Wind Engineering 1 [31] Technical University of Denmark 1 [6] Huazhong University of Science and Technology 1 [32] Iowa State University, Icing Wind Tunnel 1 [33] WiST Lab, Iowa State University 1 [34] Von Karman Institute 1 [35] Department of Engineering Science, National Cheng Kung University 1 [36] Netherlands Organisation for Applied Scientific Research (TNO) 1 [37] Politecnico di Milano, "Sergio De Ponte" Wind Tunnel 1 [38] Kyushu University, Open Circuit Wind Tunnel 1 [39] TU Delft, Open Jet Facility 1 [40] University of Liege 1 [41] University of Oldemburg 1 [42] Vrije Universiteit Brussel 1 [35] Revisión de la investigación en los túneles principales Túnel de viento de sección abierta, Mie University…”
Section: Instalación Apariciones Referenciamentioning
confidence: 99%
“…This study was made for wind turbines, although, thanks to the subsonic velocity regime, it could also be applied to ground vehicles. In their other [81] work, they studied the height and boundary layer ratio for wind turbines. The requirements and goals were different, but they concluded that the drag was reduced by the most (84.9-83.2%) when the height of the VG height was between the 66-100% of the total height of the boundary layer, while the installation angle did not affect the C D [82].…”
Section: Topology Modificationmentioning
confidence: 99%